W-band rectangular ring-bar structure with straight-edge connections - Aditya, Sheel (2013)
A square cross section ring-bar slow-wave structure with straight-edge connections has been simulated with a cylindrical electron beam for application in a traveling-wave tube amplifier. An electric field probe has been designed for coupling between the square ring-bar and a WR-10 rectangular waveguide. The saturated output peak power varies from 9.1 W to 28.6 W over the frequency range of 90 - 98 GHz for a beam of 19.7 kV and 20 mA.